Physiological profile of the Norwegian taekwondo (ITF) national team - Iversen, Vegard V.; Hafstad, Arild B.; Falco, Coral; Kristoffersen, Morten (Frontiers in Physiology, 2025)
IntroductionThis study aimed to assess the physiological profile of the Norwegian National Taekwondo Team (ITF).MethodsThirty-three athletes (Age = 20.8 ± 4.4), participated in the study, including 19 females (Age = 20.4 ± 3.4) and 14 males (Age = 21.6 ± 5.5). The athletes performed anthropometric and body composition, counter movement jump, maximal oxygen consumption (VO2max), leg press, brutal bench, and pull-ups tests. A Univariate Analysis of Variance (ANCOVA) was conducted to examine the effects on gender (male, female), experience (junior, senior), and competition level (medalists, non-medalists) on the outcome variables.ResultsAthletes demonstrated the following anthropometric and physical characteristics: weight (males: 72.7 ± 11.7 kg; females: 61.7 ± 10.5 kg), height (males: 179.2 ± 5.3 cm; females: 168.9 ± 8.5 cm), body fat (males: 9.5% ± 4.4%; females: 18.6% ± 4.9%), VO2max (males: 58.8 ± 7.3 mL/kg/min; females: 50.5 ± 4.1 mL/kg/min) brutal bench (males: 15.6 ± 5.7 reps; females: 14.9 ± 8.9 reps), pull-ups (males: 11.4 ± 5.0 reps; females: 13.0 ± 9.3 reps), CMJ (males: 42.1 ± 4.8 cm; females: 31.1 ± 3.3 cm), maximum load (males: 234.0 ± 54.2 kg; females: 168.5 ± 33.6 kg), peak power (males: 1475.6 ± 390.0 W; females: 918.4 ± 162.4 W), and normalized peak power (males: 20.1 ± 2.8 W/kg females: 15.0 ± 1.6 W/kg).ConclusionWhile physiological parameters show differences based on gender, they do not discriminate for competition level neither experience. Nevertheless, the Norwegian national team exhibit levels of physical and physiological conditions aligned with other elite athletes in other combat sports. The results provide valuable insights into the physiological levels that elite ITF taekwondo athletes should attain.